The Effect of Good Corporate Governance and Implementation of Green Accounting on Employee Performance at PT Nusamas Jaya Lestari - Erni; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
The purpose of this study is to determine whether Good Corporate Governance and Green Accounting Implementation have a significant effect on Employee Performance at PT Nusamas Jaya Lestari. This study uses quantitative data methods and the data source is primary data. The population in this study were all permanent employees who worked at PT Nusamas Jaya Lestari as many as 101 employees. The sample in this study were all permanent employees who worked at PT Nusamas Jaya Lestari, totaling 101 respondents using saturated sample data collection techniques. Data analysis and testing consists of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple linear regression analysis, partial (T test) and simultaneous (F test) hypothesis testing, and determination coefficient tests. The results of this study indicate that Good Corporate Governance has a partially significant effect on Employee Performance with a calculated T value of 2,042 > T table 1,984 and a significant value < 0,05, namely with a value of 0,044 < 0,05. Green Accounting has a partially significant effect on Employee Performance with a T value of 3,832 > T table 1,984 and a significant value < 0,05, namely with a value of 0,000 < 0,05. Good Corporate Governance and Green Accounting simultaneously have a significant effect on Employee Performance with an F value of 14,992 > F table 3,09 and a significant value < 0,05, namely with a value of 0,000 < 0,05. The regression coefficient value is 23,4%.